Analysis Supply Chain Management of Organic Pakcoy - Megawati Citra Alam; Budi Utomo; Aflahun Fadhly Siregar; Mochammad Agus Santoso (JASc (Journal of Agribusiness Sciences), 2021)
Vegetables are a potential commodity. Pakcoy is one of the commodities have high deman. Because of high demand, quality assurance, insufficient supply and delivery that is not on time are the causes of the inefficient performance of Pakcoy's supply chain. Therefore, this study aims to identify and study the organic pakcoy management chain in the Brenjonk Organic Community. Respondents in this study were organic pakcoy farmers in the Trawas and Pacet areas, Brenjonk Organic Community, PT Y, and supermarkets. This research was conducted by using descriptive analysis method of Food Supply Chain Networking (FSCN) framework, trading system analysis, and descriptive analysis using attribute suitability. Discussion on organic pakcoy supply chain management at the Brenjonk Organic Community using the FSCN framework for chain analysis, business chain processes and supply chain performance analysis. Chain goals include market targets, development goals, and partnership development. Based on the results of this analysis, the management of the organic supply chain has not been going well because the supply chain is still too long.